Advances in sustainable materials and structural hydraulic performance for resilient infrastructure systems - Putra Jaya, Ramadhansyah; Munirwan, Reza Pahlevi; Bunyamin, Bunyamin (Popular Scientist, 2025)
This issue of Smart and Green Materials Journal brings together a diverse yet coherent collection of studies that collectively advance sustainable materials and structural hydraulic performance for resilient infrastructure systems. The contributions span material innovation, performance optimization, and experimental validation across concrete technology, pavement engineering, masonry materials, timber structures, and open-channel hydraulics. Several articles address the sustainability and performance of cement-based systems through improved curing strategies, internal curing using super-absorbent polymers, optimized sand grading, and the incorporation of natural fibers as eco-friendly reinforcements. Complementing these efforts, the mechanical characterization of indigenous timber species and the reuse of reclaimed asphalt pavement as recycled aggregates highlight the role of locally sourced and recycled materials in reducing environmental burdens while maintaining structural reliability. Extending beyond material behavior, this issue also includes an experimental investigation into hydraulic jumps over rough and sloped beds, emphasizing the importance of boundary conditions in energy dissipation and flow stability. Together, these studies demonstrate how sustainable material choices and performance-oriented design can be synergistically applied to develop infrastructure systems that are both environmentally responsible and resilient to increasing operational demands.